A mixed methods study of lived experiences of homelessness in Wales and childhood adversity. (20th October 2021) - Grey, CNB; Woodfine, L; Davies, AR; Azam, S
Abstract: Background: Homelessness is a serious and complex societal and public health issue with multiple causes and solutions. Dealing with homelessness involves both supporting people at risk of homelessness and addressing personal and structural causes occurring through the life-course, including Adverse Childhood Experiences (ACEs). We examine the relationship between ACEs and homelessness in Wales, and consider priority areas for early intervention and prevention. Methods: Data was retrospectively analysed from a 2017 cross-sectional national 2017 (n = 2452) of adults aged 16-69 years living in Wales using a stratified random probability sampling methodology. Outcome measures included number of ACEs, lifetime homelessness, and childhood resilience assets and were analysed using bivariate statistics. Pathways interviews with people experiencing homelessness (n = 27) and services (n = 16) explored experiences and views, and were analysed thematically. Results: Homelessness affects 1 in 14 (7%) of the Welsh population in their lifetime. 87% of those with lived experience of homelessness had experienced at least one ACE compared with a Welsh average of 46%; and 50% of those with lived experience of homelessness had experienced 4+ ACEs, compared to 11% in the wider population. Compared with those with no ACEs, individuals with 4+ ACEs were 16 times more likely to report experiencing homelessness (95% CI 9.73, 26.43), but Childhood Resilience Assets were protective reducing this by half (adjusted odds ratio 8.073, 95% CI 4.68, 13.93). From interviews, early years/schools are critical in supporting children with ACEs, and services through the life-course need to be ACE-aware and better able to cope with impacts of ACEs. Conclusions: A clear association is seen between ACEs and homelessness. Early intervention that prevents ACEs is needed, as well as better addressing support needs of both child and adult vulnerable populations to prevent homelessness and intervene earlier. Key messages: In a national Welsh study, 87% of those reporting lived experience of homelessness had experienced at least one adverse childhood experience (ACE), and 50% reported four or more ACEs. Early intervention that prevents ACEs, combined with a trauma-informed approach that builds resilience in at-risk children and adults, is likely to contribute to reducing and preventing homelessness.